2016
DOI: 10.1177/0972150916631208
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Climate and Its Impact on Learning in Teams in Business Organizations

Abstract: Learning in an organization takes place at the individual, group and organizational levels. There is an upsurge of interest among researchers in issues of collective learning. Spirituality at work, also a multilevel phenomenon, manifests at both the individual and the collective levels. Spirituality at work is about search for meaning or higher purpose, connectedness and transcendence. Spirituality is recognized as a major factor in learning at the individual level. However, the expression and impact of spirit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Many (73.4%) of the participants identified that a diverse set of spiritual views were accepted in their clinical site. This is important as organisational psychology research recognizes the value of staff being able to realize and value the spiritual dimensions to their practices and be supported in doing so by their employers and managers (Pandey, Gupta, & Kumar, 2016). Previous work also links spiritual climate with a positive effect on work‐related satisfaction (Albashayreh, Al Sabei, Al‐Rawajfah, & Al‐Awaisi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many (73.4%) of the participants identified that a diverse set of spiritual views were accepted in their clinical site. This is important as organisational psychology research recognizes the value of staff being able to realize and value the spiritual dimensions to their practices and be supported in doing so by their employers and managers (Pandey, Gupta, & Kumar, 2016). Previous work also links spiritual climate with a positive effect on work‐related satisfaction (Albashayreh, Al Sabei, Al‐Rawajfah, & Al‐Awaisi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Pandey, Gupta, and Kumar (2016) developed the four constructs that are practised as spirituality in the workplace. The authors noted that the constructs include connecting people for wellbeing, developing a sense of authenticity, sense of community, and gratefulness (Pandey, Gupta, & Kumar, 2016). Furthermore, it has been proposed that employees work meditatively, therefore, employees could become engaged with the organization.…”
Section: Ws -Indian Contextmentioning
confidence: 99%
“…Also, quite a few other studies seek to investigate the relationship that workplace spirituality has with organizational performance (Giacalone and Jurkiewicz 2004;Duchon and Plowman 2005;Garg 2017), and with organizational development (Pawar 2008). Other studies have also investigated and found an encouraging association between WSP and other dimensions of the workplace like leadership perspective (Sengupta 2010); leadership effectiveness (Abdullah et al 2009); knowledge-sharing intention and transformational leadership (Khari and Sinha 2017); emotional intelligence (Pradhan and Jena 2016); team learning (Pandey et al 2016; Garg and Saxena 2019); employee well-being (Garg 2018); and low incidences of absenteeism (Chawla and Guda 2010;Pawar 2009). It is quite evident from past research that workplaces practicing spirituality have not only satisfied and more involved employees but also a more committed and productive workforce.…”
Section: Workplace Spirituality and Work Attitudes (Constructive Devimentioning
confidence: 96%
“…The concept of authenticity is used both in psychology as well as existentialist philosophy. It refers to the harmonization of the actions and behaviors of the executives in an organization with their central and internalized cultural values and belief systems (Pandey et al 2016). It is what other people see in you, and can, therefore, be controlled by you, to a great extent.…”
Section: Authenticitymentioning
confidence: 99%